1989
DOI: 10.3919/ringe1963.50.148
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Pedunculated Hepatocellular Carcinoma, and Reveiw of 62 Cases Reported in the Japanese Literature

Abstract: A 71-year-old man visited our hosptial with the chief complaint of a mass in the left epigastric region. MDL revealed a compresed area ranging from the fundus ventriculi to the corpus ventriculi, and CT revealed a giant mass with an uneven interior. Angiography revealed dilatation of the celiac, splenic and hepatic arteries and indicated that the tumor mass was nourished mainly by the splenic artery. Because gastric sarcoma was suspected, surgery was performed on the patient. The mass, which was found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…1,2 In a review of 62 patients with pedunculated HCC carried out by Touchika et al, 12 intrahepatic recurrence was observed in 22 patients (35.4%), and distant organ metastases was seen in 14 patients (22.5%). 12 Based on the high incidence of the presence of portal vein infiltration and intrahepatic metastases in resected specimens and the prognosis after hepatectomy, Kan et al 13 reported that systematic hepatectomy was more suitable than partial hepatectomy as a treatment modality for pedunculated HCC. From these observations, we believe that the lack of recurrence in the remnant liver in our patient may have been, in part, dependent on the surgical procedure selected.…”
Section: Discussionmentioning
confidence: 92%
“…1,2 In a review of 62 patients with pedunculated HCC carried out by Touchika et al, 12 intrahepatic recurrence was observed in 22 patients (35.4%), and distant organ metastases was seen in 14 patients (22.5%). 12 Based on the high incidence of the presence of portal vein infiltration and intrahepatic metastases in resected specimens and the prognosis after hepatectomy, Kan et al 13 reported that systematic hepatectomy was more suitable than partial hepatectomy as a treatment modality for pedunculated HCC. From these observations, we believe that the lack of recurrence in the remnant liver in our patient may have been, in part, dependent on the surgical procedure selected.…”
Section: Discussionmentioning
confidence: 92%